2017
DOI: 10.3233/jad-160567
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid-Enriched Extracellular Vesicles and Alzheimer’s Disease: A Decade of Research

Abstract: Extracellular vesicles (EVs), particularly exosomes, have emerged in the last 10 years as a new player in the progression of Alzheimer’s disease (AD) with high potential for being useful as a diagnostic and treatment tool. Exosomes and other EVs are enriched with the sphingolipid ceramide as well as other more complex glycosphingolipids such as gangliosides. At least a subpopulation of exosomes requires neutral sphingomyelinase activity for their biogenesis and secretion. As ceramide is often elevated in AD, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 108 publications
(159 reference statements)
0
61
0
Order By: Relevance
“…Quantification of complex lipids in human milk shows that sphingomyelin is the most abundant, making up about 36% of complex lipids, followed by glycerophospholipids, phosphatidylethanolamine (29%), and phosphatidylcholine (25%) [23,32,33]. Exosomes are also enriched with sphingolipids, particularly ceramide and sphingomyelin, and glycerophospholipids such as phosphatidylserine [34]. Like fatty acid levels, the composition of sphingolipids in breast milk can also be modified by diet.…”
Section: Complex Lipids In Breast Milkmentioning
confidence: 99%
“…Quantification of complex lipids in human milk shows that sphingomyelin is the most abundant, making up about 36% of complex lipids, followed by glycerophospholipids, phosphatidylethanolamine (29%), and phosphatidylcholine (25%) [23,32,33]. Exosomes are also enriched with sphingolipids, particularly ceramide and sphingomyelin, and glycerophospholipids such as phosphatidylserine [34]. Like fatty acid levels, the composition of sphingolipids in breast milk can also be modified by diet.…”
Section: Complex Lipids In Breast Milkmentioning
confidence: 99%
“…Wang et al, 2012). To date, inhibition or genetic deficiency of nSMase2 is a method widely used to prevent exosome secretion in various cell types and tissues (Chairoungdua, Smith, Pochard, Hull, & Caplan, 2010; Dinkins et al, 2014; Dinkins, Enasko, et al, 2016; Dinkins, Wang, & Bieberich, 2016; Goldkorn, Chung, & Filosto, 2013; Guo, Bellingham, & Hill, 2015; Kong, He, et al, 2015; Kosaka et al, 2010; Marsh & van Meer, 2008; Menck et al, 2017; Shamseddine, Airola, & Hannun, 2015; Tan et al, 2013; Trajkovic et al, 2008; Yuyama, Sun, Mitsutake, & Igarashi, 2012). nSMase2 converts sphingomyelin into ceramide, a reaction shown to be instrumental for exosome secretion in vitro (Trajkovic et al, 2008) (Fig.…”
Section: Got Exosomes: What’s (Really) In Your Prep?mentioning
confidence: 99%
“…1A). Our laboratory showed that inhibition and genetic deficiency of nSMase2 also suppresses exosome secretion in vivo (Dinkins et al, 2014; Dinkins, Enasko, et al, 2016; Dinkins, Wang, et al, 2016). These discoveries and the critical role of ceramide for the function of exosomes, particularly in cancer, will be discussed in the next sections of this review.…”
Section: Got Exosomes: What’s (Really) In Your Prep?mentioning
confidence: 99%
“…The process by which Aβ binds to exosomes is complex. Glycosphingolipids (GSLs), which are involved in exosome release mechanisms, bind to cytosolic Aβ and are present both in the cell membrane and in exosomes (Dinkins, Wang, & Bieberich, 2017). Degradation of GSL-glycans with endoglycoceramidase (EGCase) prevent the association between Aβ and exosomes (Yuyama et al, 2015;Yuyama & Igarashi, 2017).…”
Section: Exosome Cargo In Ad and Ds-admentioning
confidence: 99%